2018
DOI: 10.1177/0361198118796025
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Impact of App-Based Ride Share Systems in an Urban Context: Findings from Austin

Abstract: App-driven ridesharing platforms are gaining popularity and are transforming urban movement patterns in cities throughout the world. Because of privacy and business considerations, their owners have released little information about riders’ trip-making characteristics. This lack of data prevents planners and modelers from understanding and quantifying the impact of these new modes on regional travel patterns. In 2016, RideAustin, a not-for-profit company, was established to provide mobility-on-demand services … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(29 citation statements)
references
References 2 publications
2
27
0
Order By: Relevance
“…While still up for debate, some argue that RH may actually serve to reduce automobile usage, as it discourages vehicle ownership and eliminates much of the wasteful driving associated with the search for parking (Anderson, 2014). Moreover, by stressing its gap-filling potential, others believe that RH complements more than it substitutes transit use, and may increase accessibility for carless individuals in areas with poor transit supply (Feigon and Murphy, 2016;Komanduri et al 2018).…”
Section: Equity In Transportationmentioning
confidence: 99%
See 1 more Smart Citation
“…While still up for debate, some argue that RH may actually serve to reduce automobile usage, as it discourages vehicle ownership and eliminates much of the wasteful driving associated with the search for parking (Anderson, 2014). Moreover, by stressing its gap-filling potential, others believe that RH complements more than it substitutes transit use, and may increase accessibility for carless individuals in areas with poor transit supply (Feigon and Murphy, 2016;Komanduri et al 2018).…”
Section: Equity In Transportationmentioning
confidence: 99%
“…Others, however, have drawn much more optimistic conclusions with regards to the modal impacts of RH, suggesting that it will act as a complement, rather than a substitute to transit. Proponents of this view emphasize the potential of RH to serve as the first/last mile of transit trips, and its ability to provide access to carless individuals in areas with low transit supply (Feigon and Murphy, 2016;Komanduri et al, 2018).…”
Section: Modal Equitymentioning
confidence: 99%
“…By comparing RH travel-times to their fastest transit alternatives, they further showed that 66% of their 283 surveyed RH trips would have been twice as long if conducted by public transit, and this led them to believe that RH may be filling a gap in areas where public transit and traditional taxi services are sparse. Differences in traveltime are further used to establish the gap-filling potential of RH in a study by Komanduri et al (2018), which focuses on the not-for-profit RH company called RideAustin in Texas. They found that a majority of transit trips were slower by 40% or more when compared to equivalent RideAustin trips, and establish this without accounting for transit reliability (i.e.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Others, however, have refuted this concern by emphasizing the ability of RH to act as a supplement to transit; noting that RH can provide first/last mile services and deliver services that are not directly competing with existing transit lines (Rayle et al, 2016;Feigon and Murphy, 2016;Komanduri et al, 2018;Young, 2019). These benefits have gained considerable traction among transit agencies seeking to reduce operational costs as well as among policymakers charged with the difficult task of effectively regulating RH services.…”
Section: Introductionmentioning
confidence: 99%
“…For example, public transport smart cards simplify travelling for users, while behind-the-scenes, the cards provide valuable data for route planning. Ride-sharing applications (apps) also have transformed urban movement patterns [17]. Yet, there is great scope to extend the use of these technologies; specifically, there is very little evidence showing that cities are using such practices to improve the efficient use of Shadeways, which can eventually lead to increased adaptation to excess heat in urban areas.…”
Section: Introductionmentioning
confidence: 99%